Historical Fictions and Hellenistic Jewish Identity : Third Maccabees in Its Cultural Context - Johnson, Sara Raup (Book collections on Project MUSE., 2005)
In this thoughtful and penetrating study, Sara Raup Johnson investigates the creation of historical fictions in a wide range of Hellenistic Jewish texts. Surveying so-called Jewish novels, including the Letter of Aristeas, 2 Maccabees, Esther, Daniel, Judith, Tobit, Josephus's account of Alexander's visit to Jerusalem and of the Tobiads, Artapanus, and Joseph and Aseneth, she demonstrates that the use of historical fiction in these texts does not constitute a uniform genre. Instead it cuts across all boundaries of language, provenance, genre, and even purpose. Johnson argues that each author us.